Psychological distress of mothers of disabled children: an exploration - Greeshma K (Department of Psychology, University of Calicut, 2023)
Research work in the area of disability, especially in developmental disability is very limited in Kerala. Among the published studies, most of them focus on persons with disabilities. There are very few studies that address the issues faced by their caretakers. The constant and time-consuming caretaking, additional resources for raising the child, etc., may contribute many psychological problems among caretakers. In most families, mothers are the primary caregivers who experience many issues concerning their wards. This may create negative influence on many aspects of their life, including personal, social, and economic spheres. The stress may be varied based on the type or severity of the disability. By realizing this, the researcher has scientifically studied the personal and social problems experienced by mothers of children with disabilities.The study followed a mixed-method design for understanding the psychological distress of mothers of children with disabilities. The present research is composed of two sections-a qualitative phase and a quantitative phase. To study the experiences of mothers, 21 mothers of differently-abled children were met directly and information was collected scientifically. The data were coded using the thematic analysis method. Then, based on this information and based on previously published studies in this field, research instruments were prepared and collected. Information from 289 mothers was collected through the survey method. Data were analyzed using various statistical methods including ANOVA and correlation and conclusions were reached.The findings of the study have revealed that mothers experience psychological distress in a variety of means. Societal, personal, and child-related factors play a role in stress levels. It was found that being labeled as the mother of a differently-abled child has an impact on their psychological distress. They also face problems economically, physically, cognitively, and emotionally. It has also been found that family support, confidence as an effective parent, positive thoughts, spirituality, and religious practices help to some extent in overcoming such problems. Likewise, the lack of clear knowledge about the disability of these children and the lack of understanding of how to deal with it can add fuel to the mothers' mental distress. Financial difficulties and health problems in the family also often lead to distress.To study more on the relevant topics found in the qualitative analysis, afurther quantitative study was conducted. Since there were no appropriate instruments for Affiliate Stigma and Parental Self-efficacy, the researcher developed instruments for these two variables in Malayalam. Then the data were collected using the Perceived Social Support Scale, the Affiliate Stigma Scale, the Parental Self-Efficacy Scale, and the Psychological Distress Scale. All the collected data were entered into a spreadsheet for statistical analysis. Descriptive statistics, Pearson product-moment correlation, regression (enter method), and ANOVA were used for analysis. The results revealed a significant relationship between perceived social support, affiliate stigma, parental self-efficacy, and psychological distress. The regression analysis showed that most of the dimensions of selected variables significantly predicted the psychological distress of mothers of children with disabilities. The 3-way Analysis of Variance revealed a significant interaction of perceived social support, affiliate stigma, and parental self-efficacy on the psychological distress of participants. Mothers who have high perceived social support, high parental self-efficacy, and low affiliate stigma scored low mean scores in psychological distress.While going through the results, it is clear that most of the participants in the study experience distress at varying levels. For the identification and interventions on this issue, the caregivers are also to be included in the rehabilitation programs for children with disability. While including the caregivers in the rehabilitation process, their problems should also be addressed. Most of the study participants perceived professional support as great support. In this way, if professional support can be arranged at the government level for everyone, the difficulties may be eased. Most of them adapt to the stress by having a hopeful approach to life, learning about the disability and how to deal with it, trying to get to know it, ensuring family or partner support, and spirituality. Meanwhile, stress has been reported to be higher in those who get involved without trying to figure out the problem. Furthermore, Psychological distress is reduced when it includes better family support, a social environment, and belief in one's abilities. Based on these observations, stress management programs/training programs can be developed.
Thesis (Ph.D)- University of Calicut, Department of Psychology, 2023
Keywords: Affiliate stigma; Exploration; Mothers of children with disabilities; Parental self-efficacy; Perceived social support; Psychological distress